Raton Day Tour Two: Nearby Adventures From Raton 2 - Carroll, William; Coda Publications; William Carroll (Raton, New Mexico Coda Publications, 2008)
Raton Day Tour Two takes you to much of the best surrounding New Mexico's finest city. Wader through the Marchiondo store, enjoy Cimarron's Community Day, count bullet holes in the St. James HOtel, be awed by the Dawson Mine site and cemetery, ruins of Colfax, explore an 1860 grist mill and picnic with the families of isolated Tinaja. Over an hour-long DVD loaded with pleasant adventure in Northeastern New Mexico.
William Carroll
Keywords: William Carroll; Raton, NM; Marchiondo; Cimmaron, NM; St. James Hotel; Dawson Mine and cemetery; Colfax, NM; Tinaja, NM. -- Northeastern New Mexico; Raton, New Mexico; Cimmaron, New Mexico; Dawson, New Mexico; Tinaja, New Mexico; Colfax, New Mexico. -- Northeastern New Mexico